FRI0027 The Inflammatory Pathology of Lupus Nephritis Is Significantly Induced with Psychosocial Stress, Suppressed with Exercise, and Correlates with TNF-Alpha and MCP-1 Expression in A Murine Model. (15th July 2016) - Aqel, S.; Hampton, J.; Valiente, G.; Sheridan, J.; Jarjour, W.; Young, N.A.
Abstract : Background: Studies incorporating either regular exercise or stress modification programs have been efficacious in influencing the clinical disease course of systemic lupus erythematosus (SLE). We have previously demonstrated in mice that daily, moderate exercise limits inflammation systemically and that repeated social stress stimulates proinflammatory responses. Objectives: To determine if daily moderate exercise (DME) or psychosocial stress can significantly affect chronic autoimmune-mediated inflammation, we examined the NZM2410 mouse model of lupus nephritis, which spontaneously develops severe, early-onset glomerulonephritis at 22–40 weeks of age. Methods: All mice were removed from the study when experimental removal criteria was reached [blood urea nitrogen (BUN)>50 μg/mL; weight loss>20%]. The DME protocol consisted of daily 45 min treadmill walks at moderate intensity (8 m/min) beginning at 18 weeks of age. To disturb the social order within an established social hierarchy, an aggressive intruder was introduced to induce repeated social disruption stress (SDR). SDR was performed daily for 6 consecutive days beginning at 20 weeks of age. When SDR mice met experimental removal criteria, an age-matched control counterpart was selected at random for comparative analysis. Kidney tissue and serum were collected at experimental endpoint. Multi-plex ELISA measurements of cytokine expression were performed on serum samples. Results: Glomerulonephritis was enhanced with SDR, but significantly improved with DME, as indicated by IgG and C3 complex deposition. Histopathological examination of renal tissue showed glomerular hypercellularity and hyperplasia of the Bowman's capsule. Furthermore, BUN and weight measurements showed a 42% improvement with DME at 43 weeks of age. Immunohistochemical analysis and digital image quantitation of macrophage-mediated inflammatory responses in the kidney revealed a significant induction with SDR and suppression with DME. Additionally, serum cytokine analysis showed up-regulation of IL-5, IL-6, IL-10, and TNF-α with SDR and in older NZM2410 mice relative to younger mice and wild-type controls. While levels of IL-6 were not reduced, expression of IL-5, IL-10, and TNF-α was suppressed with DME. Since TNF-α induces monocyte chemoattractant protein-1 (MCP-1) secretion, MCP-1 expression was measured and demonstrated a reduction with DME and enhancement following SDR. Conclusions: Our data suggests that renal histopathology can be modified via exercise and stress reduction by suppressing TNF-α induction and expression of MCP-1. Thus, stress reduction and moderate exercise could be used therapeutically in adjunct to pharmacological therapy to help control the chronic inflammation associated with lupus nephritis and other autoimmune diseases. References: Blazek, A, et al. Exercise Suppresses Systemic Inflammation via Inhibition of Nf-Kb Activation in Monocytes. Ann Rheum Dis 2014;73:Suppl 2 102 doi:10.1136/annrheumdis-2014-eular.3914 Powell, ND, et al., Social stress up-regulates inflammatory gene expression in the leukocyte transcriptome via beta-adrenergic induction of myelopoiesis. Proc Natl Acad Sci U S A, 2013. 110(41): p. 16574–9. Acknowledgement: The Ohio State University Wexner Medical Center Disclosure of Interest: None declared